Flow rate modulates focused ultrasound-mediated vascular delivery of microRNA - Stephanie He; Davindra Singh; Brandon Helfield (Molecular Therapy: Nucleic Acids)
Gene therapy targeting ischemic heart disease is a promising therapeutic avenue, but it is mostly restricted to viral-based delivery approaches which are limited due to off-target immunological responses. Focused ultrasound presents a non-viral, image-guided technique in which circulating intravascular microbubble contrast agents can reversibly enhance vascular permeability and gene penetration. Here, we explore the influence of flow rate on the microbubble-assisted delivery of miR-126, a potent pro-angiogenic biologic, using a custom acoustically coupled pressurized mesenteric artery model. We demonstrate that under the same ultrasound conditions, increased flow rates enhance microbubble-mediated cell permeability; yet, miR-126 delivery itself exhibits a negative correlation with increasing flow velocity. Post-ultrasound assays confirmed vessel vasoreactivity, maintaining vasoconstriction and vasodilation capacities. These findings underscore the critical role microbubble flow rate plays in focused ultrasound gene therapy, especially notable for applications in which blood velocity itself is a salient pathophysiological indicator of disease progression, including ischemia.